2007
DOI: 10.1088/1742-6596/86/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of the plasma series resonance effect in radio-frequency discharges

Abstract: The intention of the paper is to give an example on how different plasma diagnostics can be combined in a synergistic way in order to investigate new physics. The link between the individual diagnostics has to be provided by theoretical concepts that predict certain relations between the different plasma parameters. The example chosen here is the effect of self-excited plasma series resonances in asymmetric capacitively coupled RF discharges. These resonance oscillations lead to high frequency current oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 35 publications
1
83
0
2
Order By: Relevance
“…It also results in different axial profiles of the electric field during sheath expansion and collapse. Similar asymmetries have been observed experimentally by laser electric field measurements before [5,34,35], but have neither been explained nor considered in models to describe electron heating in CCRF plasmas yet. This asymmetry is more pronounced in helium compared to argon due to the presence of the field reversal during sheath collapse, which effectively reduces the absolute value of the electric field in the horizontal layer located around the position of maximum sheath width during sheath collapse.…”
Section: Electron Heating Mechanismssupporting
confidence: 54%
“…It also results in different axial profiles of the electric field during sheath expansion and collapse. Similar asymmetries have been observed experimentally by laser electric field measurements before [5,34,35], but have neither been explained nor considered in models to describe electron heating in CCRF plasmas yet. This asymmetry is more pronounced in helium compared to argon due to the presence of the field reversal during sheath collapse, which effectively reduces the absolute value of the electric field in the horizontal layer located around the position of maximum sheath width during sheath collapse.…”
Section: Electron Heating Mechanismssupporting
confidence: 54%
“…This is caused by the rather long mean free path of the electrons (λ mf p ≈ 7 mm L b ≈ 10 mm at 10 Pa). Therefore, fast electrons, which are accelerated in the sheath regions [36,[52][53][54][55][65][66][67][68][69][70][71][72][73][74][75][76][77], ionize the background gas within the entire plasma bulk region and the common diffusion profiles are obtained for the positive ions. The negative ions are confined within this region; due to their low kinetic energy, they cannot penetrate into the sheath regions, where the time averaged potential is much lower than the plasma potential in the bulk.…”
Section: Control Of the Density Profilesmentioning
confidence: 99%
“…Electron heating at the powered and grounded electrode sheath [52][53][54][55][65][66][67][68][69][70][71][72][73][74][75][76][77] leads to a negative and positive current, respectively. Figure 8 (a) shows the measured discharge current as a function of time within one low frequency period at 100 Pa.…”
Section: Control Of the Electrical Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Several numerical and modeling studies have been reported [17][18][19][20][21][22] to study the heating mechanism by PSR in asymmetric CCRF plasma ignoring the plasma sheath at the grounded electrode by considering the grounded electrode is infinitely larger than the powered electrode. Although many reactive ion etchers use CCRF plasma discharge, which is off course finite asymmetry, studies on such plasmas to understand the different mechanism like generation of dc self-bias, PSR effect, etc., are scanty.…”
mentioning
confidence: 99%